INTERPRETASI DAN MIS INTERPRETASI BANTUAN LUAR NEGERI â€œSTUDI KASUS: IMPLEMENTASI PROGRAM POLICY ADVICE FOR ENVIRONMENT AND CLIMATE CHANGE (PAKLIM) III DI KOTA MALANGâ€ - Sugianto, Dedy; Khurun'in, Irza; Najwah, Lia Nihlah (Department of International Relations, Brawijaya University, 2019)
Implementation is a fairly important process in carrying out a decision. The implementation process will only start when the goals and objectives have been set, the activity program has been arranged and funds are ready and channeled to achieve the goals. Effective implementation is a must because, without effective implementation, decisions taken later will not be successfully implemented. If a policy/program does not function as it should, in the sense that the program cannot reduce existing problems, it can be said that the policy/program fails, but even a good policy/program can fail if implemented in an inappropriate manner. One thing that has become a problem in Malang regarding the implementation of PAKLIM foreign aid is that its implementation is not optimal.